Glucose transporters GLUT1, GLUT3, and GLUT4 have different effects on osteoblast proliferation and metabolism - Arponen, Milja; Jalava, Niki; Widjaja, Nicko; Ivaska, Kaisa K. (Frontiers in Physiology, 2022)
Bone is an active tissue that undergoes constant remodeling. Bone formation requires energy and one of the energy sources of bone-forming osteoblasts is glucose, which is transported inside the cells via glucose transporters. However, the role of class I glucose transporters in the differentiation and metabolism of osteoblasts and their precursors, bone marrow mesenchymal stromal cells (BMSCs) remains inconclusive. Our aim was to characterize the expression and contribution of main class I glucose transporters, GLUT1, GLUT3 and GLUT4, during osteoblast proliferation and differentiation. To investigate the role of each GLUT, we downregulated GLUTs with siRNA technology in primary rat BMSCs. Live-cell imaging and RNA-seq analysis was used to evaluate downstream pathways in silenced osteoblasts. Glucose transporters GLUT1, GLUT3 and GLUT4 had distinct expression patterns in osteoblasts. GLUT1 was abundant in BMSCs, but rapidly and significantly downregulated during osteoblast differentiation by up to 80% (p<0.001). Similar downregulation was observed for GLUT4 (p<0.001). In contrast, expression levels of GLUT3 remained stable during differentiation. Osteoblasts lacked GLUT2. Silencing of GLUT4 resulted in a significant decrease in proliferation and differentiation of preosteoblasts (p<0.001) and several pathways related to carbohydrate metabolism and cell signaling were suppressed. However, silencing of GLUT3 resulted in increased proliferation (p<0.001), despite suppression of several pathways involved in cellular metabolism, biosynthesis and actin organization. Silencing of GLUT1 had no effect on proliferation and less changes in the transcriptome. RNA-seq dataset further revealed that osteoblasts express also class II and III glucose transporters, except for GLUT7. In conclusion, GLUT1, -3 and -4 may all contribute to glucose uptake in differentiating osteoblasts. GLUT4 expression was clearly required for osteoblast proliferation and differentiation. GLUT1 appears to be abundant in early precursors, but stable expression of GLUT3 suggest also a role for GLUT3 in osteoblasts. Presence of other GLUT members may further contribute to fine-tuning of glucose uptake. Together, glucose uptake in osteoblast lineage appears to rely on several glucose transporters to ensure sufficient energy for new bone formation.